Trends of Outdoor Thermal Discomfort in Mymensingh: an Application of Thoms’ Discomfort index (Journal of Environmental Science and Natural Resources, 2018)
Thermal comfort is considered very important in aspects of risk assessment, summertime morbidity or in building designing. The present study applied Thom’s discomfort index (DI) to assess the trend of outdoor thermal discomfort in Mymensingh City during 2006-2015. It wasfound that December to February months was comparatively comfortable, DI values were typically